2019
DOI: 10.3390/rs11131524
|View full text |Cite
|
Sign up to set email alerts
|

Ground-Based MAX-DOAS Observations of CHOCHO and HCHO in Beijing and Baoding, China

Abstract: Glyoxal (CHOCHO) and formaldehyde (HCHO) trace gases were successfully retrieved from a multi-axis differential optical absorption spectroscopy (MAX-DOAS) system in Beijing (39.95°N, 116.32°E) and Baoding (39.15°N, 115.40°E), China. The measurements of these trace gases span the period from May 2017 to April 2018. Higher levels of trace gases were observed in Beijing most likely due to increased transport and industrial activities compared to Baoding. Different time scales were analyzed from seasonal to daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 42 publications
(49 reference statements)
2
19
0
Order By: Relevance
“…HCHO showed an increase in concentration from morning to noon, with a small reduction during 10:00 to 11:00, rose again until noon (13:00) and a reduction occurred afterward followed by a rise in the evening. Several studies have reported similar trends for diurnal variation of HCHO [24,36]. SO 2 showed a steep decline from morning until noon and then increased in the afternoon.…”
Section: Diurnal Variationssupporting
confidence: 59%
See 4 more Smart Citations
“…HCHO showed an increase in concentration from morning to noon, with a small reduction during 10:00 to 11:00, rose again until noon (13:00) and a reduction occurred afterward followed by a rise in the evening. Several studies have reported similar trends for diurnal variation of HCHO [24,36]. SO 2 showed a steep decline from morning until noon and then increased in the afternoon.…”
Section: Diurnal Variationssupporting
confidence: 59%
“…Different trace gases have different correlation with temperature. The temperature and NO 2 anti correlate with each other, while HCHO and O 3 have positive correlation with temperature [24,42]. Keeping in mind the aforementioned fact the HCHO concentration should increase when moving from pre-lockdown to post lockdown phase, our results showed that there was a significant reduction in the HCHO level during Phase-1 and Phase-2, which could be related to the reduction in emissions from various sources due to the lockdown.…”
Section: Impact Of Meteorologymentioning
confidence: 55%
See 3 more Smart Citations